The emergence of the mediated poet: Leopoldo María Panero in Roberto Bolaño’s 2666 = La emergencia del poeta mediatizado: Leopoldo María Panero en 2666 de Roberto Bolaño - John BURNS (1616, 2015)
This essay analyzes the role of Leopoldo María Panero in the novel 2666 by Roberto Bolaño. As a public figure, Panero also circulates in cinema (El desencanto), in the written press and on television. The mediatized image of Panero dialogs with notions of mauditism in recent poetry, with the transition to democracy in Spain and the role of poetry in the Era of Information. It is an image that both affirms the commercialization of artistic «authenticity» and also calls it into question.